Developing a smartphone 'app' for public health research: the example of measuring observed smoking in vehicles. - Patel, Vimal; Nowostawski, Mariusz; Thomson, George; Wilson, Nick; Medlin, Hamish (Journal of Epidemiology & Community Health, 2013)
Background We have developed manual methods to gather data on the point prevalence of observed smoking in road vehicles. To enable the widespreadinternational collection of such data, we aimed to develop a smartphone application (app) for this work.Methods We developed specifications for an app that described the: (1) variables that could be collected;(2) transfer of data to an online repository; (3) user interface (including visual schematics) and (4) processes to ensure the data authenticity from distant observers.The app functionality was trial led in roadside situations and the app was made publicly available.Results The smartphone app and its accompanying website were developed, tested and released over a period of 6 months. Users (n=18) who have registered themselves (and who met authentication criteria), have reported no significant problems with this application to date (observing 20 535 vehicles as of 5 July 2012). The framework, methodology and source code for this project are now freely available online and can be easily adapted for other research purposes. The prevalence of smoking in vehicles was observed in: Poland 2.7%(95% CI 2.3% to 3.1%); Australia 1.0% (95% CI0.7% to 1.3%); New Zealand 2.9% (95% CI 2.6% to3.2%)—similar to results using pre app methods in 2011(3.2%, 95% CI 3.1% to 3.3%).Conclusions This project indicates that it can be practical and feasible for health researchers to work together with information science researchers and software developers to create smartphone apps for field research in public health. Such apps may be used to collect observational data more widely, effectively and easily than through traditional (non-electronic) methods.